A feasibility study of putting up a geothermal power plant in Valencia, Negros Oriental - Ochoa, Armando N. (Animo Repository, 1979)
Our country like other developing and oil dependent nations in the world was caught by the 1973 oil crisis struggling not only for mere sustenance but also for survival. The worldwide oil crisis has thoroughly unfolded the absolute vulnerability of our country to drastic changes in the international oil market. For, as it is, the Philippines is about 95 percent dependent on imported petroleum to fuel its developmental needs. With the country's energy consumption expected to grow at the rate of 7.6 percent annually, we can foresee that by the year 2000 our total energy requirements will amount to about five times those at present. Since it is a national policy to achieve self-reliance on energy supply, the exploitation and development of locally available indigenous energy sources becomes imperative to meet the expected demand.The proposal is for the construction and subsequent operation of two (2) - 37.5 MW Geothermal Power Plant in Valencia, Negros Oriental by the National Power Corporation utilizing the steam from the wells of the Philippine National Oil Company-Energy Development Corporation as prescribed in P.D. 1442.The frequent power failures and the presence of towns without electric power indicates a big demand for power in the area. This and the presence of sugar centrals and mining industries who are depending on their own generating units could be more economically served by a power utility.Based on the initial findings of the exploratory drilling operations in the area, there is sufficient steam available to supply the steam requirements of the plant. Using conservative estimates and assumptions, the project will already attain the 8 percent required rate of return on net generating assets in only 3 years of commercial operation. The internal rate of return using discounted cash flow method will be 17 percent. The project will be generating P 27.04 Million on its initial year of commercial operation and will be able to recover the capital investment in eight years. An economic analysis with the only